Analisis Potensi Pariwisata dan Dampak Ekonomi terhadap Masyarakat Desa Rumah Gerat, Kecamatan Sibiru-biru, Kabupaten Deli Serdang - Zahro, Siti; Khadry, Muhammad; Sembiring, Hudan Breby Br; Damanik, Astri Perisay (Tourism, Hospitality And Culture Insights Journal, 2025)
This study aims to analyze the tourism potential and its economic impact on the community of Desa Rumah Gerat, Kecamatan Sibiru-biru, Kabupaten Deli Serdang. Utilizing a qualitative descriptive method, data were collected through interviews, field observations, documentation, and scoring based on tourism development criteria. The findings reveal that Desa Rumah Gerat possesses significant natural, cultural, and artificial tourism potential, including clean rivers, lemon agro-tourism, traditional Karo herbal medicine, local dance performances, and camping grounds. The total tourism potential score reached 3,230 out of 4,600, placing the village in the high potential category with an index of 70.21%. The economic impact is evident in increased local income opportunities, job creation, and the emergence of new tourism-based micro-enterprises. However, several limitations were identified, including the absence of accommodations, limited tourism services, inadequate infrastructure, and a lack of promotional strategies and community training. The study concludes that with proper planning, infrastructure development, and community involvement, Desa Rumah Gerat has the potential to be transformed into a sustainable tourism village. These findings are expected to support stakeholders in designing strategic actions to enhance the village’s tourism appeal and economic resilience while preserving its natural and cultural integrity